The retractations - Augustinus, Aurelius Heiliger 354-430; Bogan, Mary Inez (Fathers of the church, a new translation, 1999)
CONTENTS -- INTRODUCTION -- SELECT BIBLIOGRAPHY -- THE RETRACTIONS AND NOTES -- Prologue -- BOOK ONE -- BOOK TWO -- INDICES -- Index to the Writings of St. Augustine -- Index to Holy Scripture -- General Index